Influence of intestinal microbiota on the postnatal development of enterochromaffin cells and the enteric nervous system - Mungovan, Kal A. (My University, 2013)
At birth the gastrointestinal (GI) tract is rapidly colonized by microbial organisms which exhibit considerable fluctuations in composition across the first two years of life. During this period, the enteric nervous system (ENS) continues to undergo significant structural and functional changes. In the present study, we investigated whether exposure to intestinal microbiota influences the postnatal development of the ENS. We focused our investigations on dopaminergic neurons as they are among the latest populations of neurons to differentiate during enteric development. The myenteric plexus of specific pathogen-free (SPF) and germ-free (GF) mice were examined in whole-mount preparations of the small and large intestine at three time-points: postnatal day 1 (P1), P7, and P28. The density of dopaminergic neurons did not differ significantly between SPF and GF mice in any region of the intestine examined at P1. However, at P7, GF mice had significantly fewer myenteric dopaminergic neurons in the ileum than did SPF mice, and this difference was maintained at P28.
The proportion of enteric dopaminergic neurons has been shown to be dependent upon the availability of serotonin. In the GI tract, serotonin can be of neuronal or enterochromaffin (EC) cell origin. We therefore tested the hypothesis that reductions in myenteric dopaminergic neuron densities in the ileum of GF mice were secondary to changes in enteric serotonergic neuron densities or EC cell frequencies. Neither serotonergic neurons nor EC cell numbers were affected by GF status during the postnatal period. The reduction in dopaminergic neurons seen in GF mice must therefore be attributable to a mechanism that has yet to be determined.
These findings are consistent with the notion that enteric microbiota can influence the development of late-born neuronal populations. The reduced proportion of dopaminergic neurons in the ileum of GF mice at P7 and P28 may contribute to the previously described altered motility patterns in postnatal GF mice.
Keywords: microbiota; enteric nervous system; enterochromaffin cells; dopamine; serotonin; ENS; Digestive, Oral, and Skin Physiology; Digestive, Oral, and Skin Physiology